Evaluation of Economic Sustainability of Crop and Livestock Integrated Farming Systems Under Rainfed Agriculture (Indian Journal of Animal Production and Management, 2026)
The majority of the Indian economy is in the hands of small and marginal  farmers, with 80% of total land holdings having less than 1 ha of cultivable  land. Integration of livestock with crops provides scope for effective  utilization of byproducts, which assures the profitability of the farming  system. An Integrated Farming System approach is required to enhance  the living standards of small and marginal farmers. The present study  revealed the profitable farming systems in major farming situations and  their diversification. It was observed that the farming system consisting of  seasonal crops along with dairy, sheep, and poultry was found to be more  profitable than the cultivation of crops alone. The economic sustainability  of the farming systems was evaluated through the Sustainability Value Index  (SVI). Most of the farming systems in the rainfed black soils were found to  be sustainable. However, only one farming system in rainfed red soils was  found to be sustainable.The Simpson Index of Diversification (SID) was  also assessed, and more diversification was observed in the farming systems  under rainfed red soils. The results of the study are useful for small and  marginal farmers to adopt suitable farming systems.
Keywords: Sustainable livelihoods, Integrated Farming System